Merawat Eksistensi Nilai-Nilai Budaya Nasional melalui Penguatan Kearifan Lokal - Faizal Widodo (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2020)
Looking at the historical series, especially in he 21st century with the very swift currents of globalization that have implication for the cultural context in Indonesia tradition of experiencing a shift in old cultural values, giving birth to new cultural values, direct or indirect flow of foreign cultural globalization. Directly affects the behavior patterns of individual life, and the order of community life in the socio-cultural environment especially the cultural of the Bugis Bone community at micro, national and global levels. This paper aims to reflect on the values of national culture through strengthening the local culture of Bugis Bone, national and global as well as steps that must be taken towards the direction of changing these cultural values, so that we can maintan the existence of national culture by harmonizing local wisdom culture amids the threat of globalization, and changing times. So that in the axiological dimension the changes in cultural values will continue to run positively as we hope so that in the future these cultural values will remain and become a legacy to the next generation as well as become a stepping stone to strengthen national cultural values.